The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/met11071070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Sandblasting and Turning on Compressive Strength of Thin 316L Stainless Steel Shells Produced by Laser Powder Bed Fusion

Abstract: This study evaluates the effect of post-manufacturing treatment on the compressive performance of additively manufactured components. The components were thin cylindrical shells with an aspect ratio of 25:1 manufactured using laser powder bed fusion and that were then surface treated by means of sandblasting or turning. The as-printed and subsequently surface treated samples were uniaxially compressed until failure to depict the effect of the surface condition on the compressive mechanical behavior. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Laser polishing can also be profitably used to ease the manufacture of full density or near full density components [136][137][138]. The powder bed is made up of numerous voids.…”
Section: Analysis and Applications Of Laser Polishing: Criticality An...mentioning
confidence: 99%
“…Laser polishing can also be profitably used to ease the manufacture of full density or near full density components [136][137][138]. The powder bed is made up of numerous voids.…”
Section: Analysis and Applications Of Laser Polishing: Criticality An...mentioning
confidence: 99%
“…As a crucial engineering structure, the thin-walled steel cylindrical shell has obtained widespread application in most industrial fields. This structure tends to buckle when subjected to axial compression loads, and buckling failure is a critical concern in the design work of thin-walled cylindrical shell structures [1][2][3][4][5][6]. A large number of cylindrical shell buckling experiments have been carried out, and researchers have found that the experimentally observed buckling loads are far short of the theoretical predicted buckling loads of perfect shells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For postprocessing of LPBF‐processed components, chemical (e.g., electrochemical polishing), physical (e.g., thermal spraying), or mechanical methods (e.g., blasting treatments, milling) are applied. [ 37–40 ] The mechanical method of blasting is thereby widespread as first postprocessing step after the LPBF process. [ 32,37 ] It will introduce residual compressive stress in the component surface due to plastic deformation, which has a positive effect on, e.g., hardness, fatigue, and tensile strength, as seen for other bulk materials.…”
Section: Introductionmentioning
confidence: 99%